Sistem User Management Menggunakan Mikrotik Routeros untuk Mengontrol Akses Internet Siswa pada SMK Miftakhul Huda Way Areng - Rudi Hartono; Matsna Nurul Kholidah (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of internet services in school environments requires an effective management system to ensure secure, stable, and learning-oriented access. SMK Miftakhul Huda Way Areng faces several issues, including uncontrolled internet usage, uneven bandwidth distribution, and the absence of a system capable of limiting and monitoring user activities individually. This study aims to design and implement a user-management system using MikroTik RouterOS as a solution for regulating internet access for students and teachers. The methodology includes network design, IP address configuration, hotspot authentication setup, user-profile creation, and functional system testing. The network was structured with segmented interfaces, where ether1 serves as the ISP uplink, ether2 as the administrative network, and ether3 as the hotspot network. The implementation results indicate that the system successfully enforces access restrictions based on user type, allowing a maximum of two devices for teachers and one device for students. Additionally, the system enhances network security, organizes internet usage, and simplifies monitoring tasks for administrators. In conclusion, MikroTik RouterOS–based user management is effective for controlling internet access in educational environments and can be adopted as a sustainable solution for schools.